Crowdfunding : Fundamental Cases, Facts, and Insights - Cumming, Douglas; Johan, Sofia A. (Academic Press, an imprint of Elsevier, 2020)
Crowdfunding: Fundamental Cases, Facts, and Insights presents fundamental knowledge about a maturing economic field. Assembling and arranging datasets, case analyses, and other foundational materials on subjects associated with crowdfunding, it systematically, comprehensively, and authoritatively provides access to a consistent body of crowdfunding research. With the crowdfunding industry now consolidated, this core reference can serve as the basis for research projects and applied work. Acclaim for Crowdfunding "This book provides insightful cases and statistics from around the world on how rewards and equity crowdfunding markets work. It also includes useful information on marketplace lending. It is a great resource for entrepreneurs and investors, as well as for policymakers, academics, and students."--Craig Asano, Founder and CEO, National Crowdfunding and Fintech Association "Crowdfunding offers detailed analyses of rewards and equity crowdfunding markets using statistical methods and case studies. I recommend it for academics, practitioners, and policymakers who seek a rigorous look at crowdfunding markets around the world."--Jay Ritter, Joseph B. Cordell Eminent Scholar Chair, Warrington College of Business, University of Florida- Resumé vydavatele